1957
DOI: 10.1113/jphysiol.1957.sp005825
|View full text |Cite
|
Sign up to set email alerts
|

The effects of stimulation of the carotid body chemoreceptors on pulmonary vascular resistance in the dog

Abstract: In a previous study we investigated the effects of carotid sinus baroreceptor reflexes on pulmonary vascular resistance (Daly & Daly, 1957b, c). An examination has now been made of the reflex effects of stimulation of the carotid body chemoreceptors on the lesser circulation and the results which have been briefly reported elsewhere (Daly & Daly, 1957a) are presented in this paper. METHODSDogs of 14-7-19-6 kg body weight were anaesthetized with chloralose (0-1 g/kg intravenously) after premedication with morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

1959
1959
2015
2015

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 7 publications
3
8
0
Order By: Relevance
“…This limits the interpretation of the data in terms of an awake, normally active preparation. On the other hand the older literature contains many studies comparable to the present study (Browse and Shepherd, 1966; Carmody and Scott, 1974; Daly and Daly, 1957; Daly and Ungar, 1966; Krasney, et al, 1973; Parker, et al, 1975). Regarding the potential effect of anesthesia on the sensitivity of the chemoreceptors, Landgren et al in the older literature (1954) reported that intracarotid injections of barbiturates (Dial, Nembutal, Pentothal) had no effect on the chemosensory discharge.…”
Section: Discussionsupporting
confidence: 52%
“…This limits the interpretation of the data in terms of an awake, normally active preparation. On the other hand the older literature contains many studies comparable to the present study (Browse and Shepherd, 1966; Carmody and Scott, 1974; Daly and Daly, 1957; Daly and Ungar, 1966; Krasney, et al, 1973; Parker, et al, 1975). Regarding the potential effect of anesthesia on the sensitivity of the chemoreceptors, Landgren et al in the older literature (1954) reported that intracarotid injections of barbiturates (Dial, Nembutal, Pentothal) had no effect on the chemosensory discharge.…”
Section: Discussionsupporting
confidence: 52%
“…Previous work indicates that in the dog ventilated with room air, stimulation of the carotid bodies with hypoxic blood causes a primary reflex bradycardia (Bernthal, Greene & Revzin, 1951;Daly & Daly, 1957;Daly & Scott, 1958). In the present study we have shown that, in dogs spontaneously breathing 7% 02 in N2, withdrawal of the hypoxic stimulus to the carotid body chemoreceptors by changing the perfusate from hypoxic to oxygenated blood causes an increase in heart rate.…”
Section: Resultsmentioning
confidence: 99%
“…Daly & Scott (1958, 1963 showed that the inconsistent cardiac effects were due, at least in part, to chemoreceptor excitation initiating two opposing mechanisms: the first is a direct or primary reflex effect from the carotid bodies on the heart causing bradyeardia. This response is usually only evident if changes in pulmonary ventilation are excluded (Bernthal et al 1951;Daly & Daly, 1957Daly & Scott, 1958, 1962, 1963aDowning, Remensnyder & Mitchell, 1962), and is mediated by both the vagus and sympathetic nerves (Daly & Scott, 1962;Downing et al 1962). The second mechanism includes various secondary phenomena, important among which are events initiated by reflex stimulation of respiration causing tachycardia (Daly & Scott, 1958, 1963.…”
mentioning
confidence: 99%